DRAMATISASI BISNIS INFOTAINMENT ANTARA PROFESIONALISME DAN IDEALISME - Musta’in, Musta’in (Fakultas Dakwah IAIN Purwokerto, 2011)
The dramatization in Indonesian press is not something unintentional. It seems that it isengineered by many mass media companies in this country. This happens in all parts of newsproduction, including hunting news, determining of news sources, news writing, marketing,and broadcasting. One type of news that flourished after the reform is infotainment, whichessentially combines information and entertainment. In the world of infotainment, the news ispresented to the audience in a soft way and is flowered with elements of entertainment.With this kind of packaging, infotainment can attract people’s attention. It attracts notonly teenagers, but also adults, males and females. Since so many people are attracted by thiskind of news, more and more infotainment programs are broadcasted on televisions. Thiscondition causes the growth of business sentiment on information capital.